2002
DOI: 10.1002/jmv.10084
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of viral load in neonatal herpes simplex virus infection and comparison between type 1 and type 2

Abstract: Neonatal herpes simplex virus (HSV) infection is a severe disease with high mortality and morbidity in spite of the development of effective anti-viral therapies. The viral load in neonatal herpes simplex virus (HSV) infection was measured retrospectively in 37 patients. HSV DNA copy numbers in serum and cerebrospinal fluid (CSF) were quantified using a real-time PCR assay. Patients with disseminated infection had a higher viral load in their sera. whereas patients with central nervous system (CNS) infection e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
46
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 21 publications
3
46
1
1
Order By: Relevance
“…Although many previous studies have used a conventional single-step real-time PCR assay to quantitatively detect various infectious pathogens in different clinical samples, few have been able to describe accurate copy numbers of the causative pathogens (3,4,5,6,9,15,19,21,23). In many previous studies, even though various internal controls have been used for monitoring PCR assay conditions, they have regrettably never been used for correctly determining the copy numbers of the causative pathogens (5,6,9,15,19,21,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many previous studies have used a conventional single-step real-time PCR assay to quantitatively detect various infectious pathogens in different clinical samples, few have been able to describe accurate copy numbers of the causative pathogens (3,4,5,6,9,15,19,21,23). In many previous studies, even though various internal controls have been used for monitoring PCR assay conditions, they have regrettably never been used for correctly determining the copy numbers of the causative pathogens (5,6,9,15,19,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, real-time PCR assays have been applied in routine diagnostic laboratory testing (1,10,14,16,22). In addition to conventional qualitative analysis, real-time PCR assays make it possible to perform accurate quantitative analyses with a high degree of reproducibility (3,4,5,6,9,15,19,21,23).…”
mentioning
confidence: 99%
“…It is possible that the persistently positive PCR reflects an initially high CSF viral load that is reflective of a greater degree of CNS injury and results in a longer time for achievement of an undetectable concentration. 21 Domingues et al 22 found that among 16 patients with HSV-1 encephalitis who had a mean age of 37 ± 21 years, greater than 100 copies of HSV DNA per ml in CSF was associated with decreased level of consciousness, presence of lesions detected by CT scan of brain and poor neurological outcomes. Similar studies that assess the contribution of HSV viral load to neurodevelopmental outcome or antiviral response are needed in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…3,11 Although presumed to reflect persistent viral replication, it is unclear whether the detected PCR products after therapy represent active infection, residual DNA fragments after successful treatment, or a point along a continuum between the two states. Quantitative real-time PCR, which can provide rapid detection of HSV DNA and documentation of viral load, 21 has been used successfully in pediatric 22,23 and neonatal [22][23][24] patients with known HSV CNS infections. Kimura et al 24 applied quantitative real-time PCR in a small population of neonates with HSV, showing an association between HSV-2 infection and higher neurological morbidity, CNS involvement and CSF viral load.…”
mentioning
confidence: 99%
“…Quantitative real-time PCR, which can provide rapid detection of HSV DNA and documentation of viral load, 21 has been used successfully in pediatric 22,23 and neonatal [22][23][24] patients with known HSV CNS infections. Kimura et al 24 applied quantitative real-time PCR in a small population of neonates with HSV, showing an association between HSV-2 infection and higher neurological morbidity, CNS involvement and CSF viral load. Quantitative PCR may be useful in determining the efficacy of antiviral therapy in neonatal HSV encephalitis by documenting HSV DNA levels in serial CSF samples from infected infants.…”
mentioning
confidence: 99%